Claro de tierra - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Edhasa nebulae, 2015)
The independent republics on Mars and Venus were, in fact, resentfully dependent on Earth for their mineral wealth. What happens when heavy metals are discovered on the moon?